Perception of muslim consumers towards halal branding in advertising - Izian Idris, *; Alias, S. S. *; Singh, S. K. N. * (Lifescience Global, 2020)
The study is an eye opener into areas of Islamic Marketing that are becoming more substantial and have not been addressed. In advertisements, Halal is considered a brand that holds significant value for Muslim consumers. Furthermore, Halal branding especially in advertising has emerged as a new type of marketing advertisement. Such emergence has caused businesses to reconsider their advertising approach to attract new and retain old consumers. The study is aimed at providing an enhanced understanding on the role of advertising and branding towards Halal consumption. The role is further studied upon through extensive literature review and empirical data collection involving Muslim consumers. Analysis of data collected implied that existing insights on religious consumption is lopsided compared to the blooming Halal market particularly the perception of Muslim consumers towards Halal branding. Findings thus not only affect Muslim consumers, marketers, the government but also impact the society.